1997
DOI: 10.1093/ndt/12.11.2385
|View full text |Cite
|
Sign up to set email alerts
|

Rejection rates in kidney transplant patients with and without IgA nephropathy

Abstract: Rejection rates were not reduced in patients with IgA nephropathy and survival of grafts and patients not better than for matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Seventy patients had biopsy-verified IgA nephropathy and received first kidney transplants [11]. The outcome of transplantation in this group of patients in comparison with matched controls has been presented in detail [12]. All patients had undergone renal biopsy with enough material to establish the diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Seventy patients had biopsy-verified IgA nephropathy and received first kidney transplants [11]. The outcome of transplantation in this group of patients in comparison with matched controls has been presented in detail [12]. All patients had undergone renal biopsy with enough material to establish the diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite the possibility of the detrimental effects of a recurrence, most authors agree that these patients fare well after transplantation, and it has even been suggested that recipients with IgA nephropathy may be immunologically privileged and have better graft survival than recipients with other renal diseases (4). This is, however, not a uniform finding and other studies that have formally compared graft survival in recipients with IgA nephropathy and other renal diseases have failed to demonstrate a survival advantage of IgA nephropathy patients (5)(6)(7)(8). The issue thus remains unsettled.…”
mentioning
confidence: 98%
“…Ten‐year graft survivals were excellent regardless of the type of primary diseases. Freese et al 20 . and Bumgardner et al 10 .…”
Section: Discussionmentioning
confidence: 98%